Thermo-rheological behaviour of polymer melts in microinjection moulding - Vasco, Joel Oliveira Correia (2009)
Microinjection has proven to be one of the most efficient replication methods for microcomponents and microsystems in various domains of microengineering. The use of available commercial microinjection equipment to evaluate the polymeric flow in microchannels would surely contribute to enhancing knowledge on polymeric flow at the microscale under industrial conditions. This approach is appropriate since rheological phenomena such as wall slip, surface tension, melt pressure drop and polymer flow length can be studied. These aspects are not fully dealt with in current commercial simulation software packages. In this study a micromould was designed to assess and characterize the flow in microchannels under realistic industrial conditions.